Water column chemical data of lakes and fiords along the northern coastline of Ellesmere Island (Ward Hunt Island observatory) - Vincent, Warwick; Lionard, Marie; Veillette, Julie; Hove, Patrick Van; Charvet, Sophie; Bourget, Sébastien (Canadian Cryospheric Information Network, 2011)
Water samples were taken down the water column of several lakes and fiords (Lake A, Lake B, Lake C1, Lake C2, Lake C3, Ward Hunt Lake, Disraeli Fiord, Milne Fiord and Taconite Inlet) located along the northern coastline of Ellesmere Island (Nunavut, Canada) to investigate their chemical characteristics (TN, TP, Nitrate-nitrite, SRP, DOC, TOC, DIC). Chemical analyses were processed at the National Laboratory for Environemental Testing (NLET, Burlington, Ontario, Canada) or at Institut national de la recherche scientifique-Centre Eau Terre Environnement (INRS-ETE, Québec, Québec, Canada). : Purpose: As part of the research project ArcticNet and IPY-Merge, the purpose of this study was to investigate the chemical characteristics of lakes and fjords along the northern coastline of Ellesmere Island. : Summary: Not Applicable